Communicating About Water in the Floridan Aquifer Region: Part 2—Do People Believe Water Science? - Sadie Hundemer; Shenara Ramadan (EDIS)
It is not enough for the public to know the water science that affects their lives; it is also important that they believe it. People are more apt to use water science information if they accept it as true. Moreover, when water science is rejected, policy discourse can devolve into a debate over water facts instead of weighing alternative management strategies. A 2020 study suggests that belief in regional water science is influenced by political orientation. As a result, some individuals do not believe what they understand to be the consensus of water scientists on topics pertaining to the Floridan Aquifer. Equipped with this information, water communicators can take proactive steps, prior to a potential water policy introduction, to increase the likelihood that the public will accept water science.